Собрание программно-оперативных заданий - Atkočiūnienė, Zenona; Broniukaitis, Romualdas (Knygotyra, 1988)
Program objective method is currently employed for planning the directions of overall industrial intensification and introduction of scientific and technical achievements into practice. Objective complex programs demand respective reorganization of information activities. The fundamentally new approach to data organization lies in the creation of data banks (DB) representing problem-oriented systems for collective use. The accomplished analysis of practice in creation of oriented DB shows that at present there are possibilities to create DB resting upon information resources either provided or generated on the spot, as well as on information and technological, linguistic, program, and technical supply arranged by the Republican automatic system and technical information.